(untitled) (Research, Society and Development, 2020)
Cardiovascular diseases (CVD) are among the leading causes of death in developed countries and their occurrence has increased epidemically. These can be defined as disorders of the heart and blood vessels. Among the various types, coronary diseases stand out, such as: Acute Myocardial Infarction, Stroke, and Congenital Heart Diseases. Objective: In this sense, the objective of this study is to perform an integrative review on the efficiency of physical therapy resources before and after cardiac surgery. Methodology: To achieve this goal, searches were performed in the following databases SCIELO, LILACS and PUBMED using phisiotherapy descriptors; cardiac surgery; hehabilitation, selected in English and Portuguese, were found as a universe 2,610 studies, after filtering the following subjects: available texts, year of research, type of study, language, were found 471 studies, so after analyzing them with the eligibility requirements Only 190 were selected, of which 40 were excluded from the study because they did not meet the proposed requirements, so after further analysis, 10 met the eligibility criteria. Results e discussions: It was observed that the studies selected in the proposed theme obtained positive results, with scientific evidence with the physiotherapeutic resources Cycloergometer and Noninvasive Ventilation (NIV). Conclusion: However, it is necessary to produce more scientific articles with practical content, with control groups.